2015
DOI: 10.1021/acs.jmedchem.5b01337
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule CXCR3 Antagonists

Abstract: Chemokines and their receptors are known to play important roles in disease. More than 40 chemokine ligands and 20 chemokine receptors have been identified, but, to date, only two small molecule chemokine receptor antagonists have been approved by the FDA. The chemokine receptor CXCR3 was identified in 1996, and nearly 20 years later, new areas of CXCR3 disease biology continue to emerge. Several classes of small molecule CXCR3 antagonists have been developed, and two have shown efficacy in preclinical models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 144 publications
(222 reference statements)
0
51
0
Order By: Relevance
“…31 Compound b was further modified to JN-2 (compound c), which contains an amide side chain to mimic the well-known CXCR3 antagonist AMG 487 (compound d), a small molecular antagonist that has been evaluated in Phase IIa clinical trials. 32 …”
Section: Resultsmentioning
confidence: 99%
“…31 Compound b was further modified to JN-2 (compound c), which contains an amide side chain to mimic the well-known CXCR3 antagonist AMG 487 (compound d), a small molecular antagonist that has been evaluated in Phase IIa clinical trials. 32 …”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, if future studies provide mechanistic support for a protumorigenic role of CXCR3 signaling in neurofibroma development, further exploration of CXCR3-targeted neurofibroma prophylaxis may be warranted. Small-molecule inhibitors of CXCR3 are an active area of drug development, with no serious adverse events reported in a phase I clinical trial of the CXCR3 inhibitor AMG-487 (67).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that therapy with potent smallmolecule CXCR3 antagonists showed significant efficacy in animal models of autoimmune diseases, including rheumatoid arthritis and multiple sclerosis, and in the prevention of transplant rejection. 3,[17][18][19] Cleavage of the transmembrane chemokines CXCL16 and CX3CL1 is associated with the inflammatory cascade and, therefore, the soluble form of the molecules may serve as inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%